2015
DOI: 10.1002/2015gc005734
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Late Jurassic apparent (or true) polar shift in U‐Pb‐dated kimberlites from cratonic North America (Superior Province of Canada)

Abstract: Different versions of a composite apparent polar wander (APW) path of variably selected global poles assembled and averaged in North American coordinates using plate reconstructions show either a smooth progression or a large ($30 ) gap in mean paleopoles in the Late Jurassic, between about 160 and 145 Ma. In an effort to further examine this issue, we sampled accessible outcrops/subcrops of kimberlites associated with high-precision U-Pb perovskite ages in the Timiskaming area of Ontario, Canada. The 154.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 58 publications
8
54
1
Order By: Relevance
“…Paleomagnetic data from Adria (see Channell, , for a first compilation) have been largely neglected in global‐composite APWPs, such as by Besse and Courtillot (), Kent and Irving (), and Torsvik et al (), and are therefore totally independent from them. Nevertheless, Channell et al () and Muttoni et al () have shown that Triassic and Jurassic poles from Adria map close to global‐composite APWPs, a correspondence also noted by Kent et al (). Here we show in detail that Jurassic data from Adria can be used to assess and refine the character of Jurassic APWP, especially the disputed Jurassic monster shift of Kent and Irving ().…”
Section: The Contribution Of Adriamentioning
confidence: 61%
See 3 more Smart Citations
“…Paleomagnetic data from Adria (see Channell, , for a first compilation) have been largely neglected in global‐composite APWPs, such as by Besse and Courtillot (), Kent and Irving (), and Torsvik et al (), and are therefore totally independent from them. Nevertheless, Channell et al () and Muttoni et al () have shown that Triassic and Jurassic poles from Adria map close to global‐composite APWPs, a correspondence also noted by Kent et al (). Here we show in detail that Jurassic data from Adria can be used to assess and refine the character of Jurassic APWP, especially the disputed Jurassic monster shift of Kent and Irving ().…”
Section: The Contribution Of Adriamentioning
confidence: 61%
“…These bioevents are the FO (=first occurrence) of C. mexicana minor and the FO of F. multicolumnatus , correlated to the MHTC12 sequence using magnetostratigraphy from the S'Adde section of Sardinia (Muttoni et al, ), and the LO (=last occurrence) of C. wiedmanni , estimated at ~156 Ma based on an Ar/Ar date (156.1 ± 0.89 Ma) on an ash layer at the top of the Rosso Ammonitico Medio at Kaberlaba (Pellenard et al, ), which is indicated. Also shown by gray bars are the age ranges of the 146.4 ± 1.4‐Ma Ithaca kimberlite pole (146Ik; Van Fossen & Kent, ), the 144 ± 5‐Ma Hinlopenstretet dikes pole (144Hi; Halvorsen, ), the 145.4 ± 1.4‐Ma Swartruggens‐Bumbeni kimberlites pole (145SB; Hargraves et al, ), and the 156.1 ± 1.6‐Ma Ontario kimberlites pole (156Ok; Kent et al, ). See text for discussion and additional references.…”
Section: The Contribution Of Adriamentioning
confidence: 99%
See 2 more Smart Citations
“…Kent et al 2015), and is interpreted by these authors in term of plate motion (referred as to the "Jurassic monster shift"). This unusually fast plate motion was previously undetected or only resulted in smooth variations around the Jurassic/Cretaceous boundary in previous composite APWPs, due to the smoothing of data intrinsic to the method of construction, or in the inclusion of lower quality Jurassic paleopoles.…”
Section: Publications Of the Institute Of Geophysics Polish Academy mentioning
confidence: 99%